Dancing in Your Head: An Interdisciplinary Review - Zardi, Andrea; Carlotti, Edoardo Giovanni; Pontremoli, Alessandro; Morese, Rosalba (Frontiers in Psychology, 2021)
The aim of this review is to highlight the most relevant contributions on dance in neuroscientific research. Neuroscience has analysed the mirror system through neuroimaging techniques, testing its role in imitative learning, in the recognition of other people's emotions and especially in the understanding of the motor behaviour of others. This review analyses the literature related to five general areas: I) breakthrough studies on the mirror system and its involvement in the prediction, the execution, the control of movement and in the process of "embodied simulation" within the intersubjective relationship; II) research focused on investigating the neurobiological foundations of the perceiving dance, highlighting the neural correlates of motor expertise through comparative studies on different dance styles; III) studies dealing with the viewer’s experience of dance according to specific dance repertoires, which revealed the relevance of choreographic choices for aesthetic appreciation; IV) studies focused on dance as an aesthetic experience, where both the emotional and the cultural dimension play a significant role, and whose investigation paves the way to further progress both in empirical and in phenomenological research methodologies; V) collaboration-based experiments, in which neuroscientists and choreographers developed expertise-related questions, especially focusing on the multiple phenomena that underlie motor imagery.